Unveiling the Essence of Gastronomy: A Data-Driven Exploration of Culinary Expertise in the Nordic Region - Cheryl Marie Cordeiro; Nataliya Berbyuk Lindström (Gastronomy)
The science of gastronomy is a context-sensitive and qualitative application of human knowledge. While qualitative content analysis is a widely recognized research method, it is time-consuming, and its results heavily depend on the analyst’s expertise. This study addresses these challenges by employing automated content analysis (ACA), including tools like VOSViewer and AntConc, alongside qualitative methods from systemic functional linguistics (SFL). By analyzing 25 interviews with various professionals in gastronomy, the research aims to reduce subjectivity in interpreting data and uncover the essence of being a gastronomic chef. The findings highlight the complexity of a chef’s role, emphasizing creativity, collaboration, and innovation as key factors in delivering exceptional service and crafting the ultimate dining experience. Understanding a chef’s knowledge is crucial for enhancing service quality and comprehending consumer behavior, which is vital for service development.